Forgotten hero [videorecording (DVD)] : Walter White and the NAACP - Morton, Joe, 1947-; Owens, Geoffrey; Rapley, Robert (PBS, 2025)
The civil rights movement was set in motion by activists of the National Association for the Advancement of Colored People. While some of its leaders are familiar, Walter White -- NAACP head from 1929 to 1955 and one of America's most influential Black men -- has been all but forgotten. The film traces the fascinating and complex life of the neglected civil rights hero.